Vindicating the right?: populism and the origins of the Tea Party Movement - Walter, Martin (2016)
Vindicating the Right? Populism and the Origins of the Tea Party Movement analyses the founding process of the Tea Party movement using the framework of populism theory. At the centre of populism theory stands the claim that populist movements frame politics as confrontation between the virtuous ‘people’ and powerful elites. The work of Ernesto Laclau and Chantal Mouffe further argues that populism is used to articulate hegemonic projects. As scholars have found, in contemporary liberal democracies populism articulates hegemonic projects that claim to represent ‘the people’ against unresponsive governments often in response to widespread dissatisfaction with democratic processes.